Pengaruh Nilai Local Wisdom Di Indonesia Terhadap Reinterpretasi Nash Syariah Dalam Pengembangan Hukum Islam - M Ridlwan Hambali (Al Hikmah: Jurnal Studi Keislaman, 2019)
Abstract, humans will not be able to escape from the rule of law that applies wherever humans live in society. Law and humans will go hand in hand. The problem is, many anomalies occur; not infrequently the law is not directly proportional to human behavior. Many texts of the Koran or as-sunnah that need to be interpreted by considering the factors of local wisdom. Synchronized with the situation and condition of Indonesian society which is geographically far and different from the situation and condition of the people of Hijaz and the Middle East. By using a historical social approach, this paper tries to present some examples of cases of differences in Indonesian society with the conditions of people living in Arabia and its surroundings where it greatly affects the differences in interpretation of Islamic texts and also influences the development of Islamic law.Keywords: Influence, Local Wisdom, Reinterpretation, Islamic Law